EVALUATION OF THE BONE MINERAL DENSITY OF ASIAN ELEPHANTS (ELEPHAS MAXIMUS) VIA DUAL-ENERGY X-RAY IMAGING OF TAILS - Chatchanok Udomtanakunchai (2019)
© 2019 by American Association of Zoo Veterinarians. Musculoskeletal problems are one of the top five causes of disease in elephants. However, recent blood chemistry analysis is the only routine protocol for bone mineral status evaluation, with no assessment method currently available for the direct measurement of elephant bone mineral density (BMD). This work applied the the dual-energy X-ray technique (DXA) technique for bone density assessment. The elephant's tail was chosen for the analysis to avoid the radiation harm. Twelve live Asian elephants (Elephas maximus) comprising eight males and four females with ages in the range of 4-77 yr were investigated. The BMD was calculated based on radiographic images acquired using the DXA technique carried out at 40 kVp 2 mAs and 50 kVp 2 mAs. Blood serum analysis of total calcium (Ca), phosphorus (Phos) and alkaline phosphatase (ALP) content was conducted in parallel with the physical examination to correlate age and BMD. Analyses produced an overall mean BMD value in the range of 0.54-1.39 g/cm2, with that of the males higher than that of the females. The BMD was found to be negatively correlated with age, Ca, and Phos, but not with ALP. In summary, the BMD analysis of an elephant's tail might be used with blood serum Ca and Phos to predict the overall bone mineral status of the animal.